2001
DOI: 10.1093/neucas/7.6.495
|View full text |Cite
|
Sign up to set email alerts
|

Does the Pre-frontal Cortex Contribute to Movement-related Potentials? Recordings from Subdural Electrodes

Abstract: The contribution of the pre-frontal cortex to movement-related potentials (MRPs) is unclear. We recorded MRPs from six subdural electrode strips placed over the frontal cortex in a 13-year-old girl being monitored prior to surgery for intractable epilepsy. MRPs were recorded prior to two types of movement: self-paced random joystick movements which involve 'what to do' and 'when to do' decision making on every trial and prior to joystick movements in a fixed forward direction triggered by a tone which does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…During the decision processes, the prefrontal area, along with other regions such as the basal ganglia, supplementary motor area, premotor area, and primary sensorimotor area, is involved [18, 23]. In electrophysiological studies with intracerebral electrodes and ECoG, the prefrontal area has been observed to be a source of the slow cortical potential and frequency power shifts in the alpha and beta bands, which physiologically implies the presence of cognitive functions such as motor planning or preparatory states before movement onset [13, 14, 33]. Through our results and by considering these points, we have demonstrated that signals from the prefrontal area can be used to predict the occurrence of motor planning or preparations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the decision processes, the prefrontal area, along with other regions such as the basal ganglia, supplementary motor area, premotor area, and primary sensorimotor area, is involved [18, 23]. In electrophysiological studies with intracerebral electrodes and ECoG, the prefrontal area has been observed to be a source of the slow cortical potential and frequency power shifts in the alpha and beta bands, which physiologically implies the presence of cognitive functions such as motor planning or preparatory states before movement onset [13, 14, 33]. Through our results and by considering these points, we have demonstrated that signals from the prefrontal area can be used to predict the occurrence of motor planning or preparations.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are reflected by an amplitude decrease in cortical rhythms that are disclosed in the alpha and beta ranges [12]. Though it is widely known that the supplementary motor, premotor, and primary sensorimotor areas can be generator sources of those two brain responses, some researchers report that the prefrontal area also contributes to their generation [1316]. However, most researches regarding the prediction of motor intention or movement type have recorded early neural signals from only the central and parietal areas covering the primary sensorimotor cortex.…”
Section: Introductionmentioning
confidence: 99%
“…BP has mostly been reported in the motor area (Deecke and Kornhuber, 1978; Roland et al, 1980; Neshige et al, 1988). However, according to more recent studies, the prefrontal cortex (PFC) is also an important area in the generation of BP (Rektor et al, 1994; Jahanshahi et al, 1995, 2001; Ryun et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The prefrontal cortex and the supplementary motor area have been assumed to play a role during preparations for self-initiated movements [18,33]. Jahanshahi et al [15] observed that self-paced joystick movements involving decision-making about precise tasks and timing induced a slowly increasing subdural positivity before movement in the dorsolateral and inferior prefrontal cortex in an epileptic patient, as indicated by MRI. Jahanshahi et al [15] observed that self-paced joystick movements involving decision-making about precise tasks and timing induced a slowly increasing subdural positivity before movement in the dorsolateral and inferior prefrontal cortex in an epileptic patient, as indicated by MRI.…”
Section: Contribution Of the Prefrontal Cortex To Movementsmentioning
confidence: 99%
“…By contrast, another study observed a decrease in the amplitude of MRCPs during muscle fatigue [12], which can be explained by a decrease in intention and habituation processes. It has been proposed that the prefrontal cortex is the brain region that formulates intentions and makes decisions before movements are initiated [13][14][15]. Thus, the choice of experimental design for the study of repetitive contractions may have a huge effect on the findings obtained on the effects of muscle fatigue on MRCP components.…”
Section: Introductionmentioning
confidence: 99%